Analisis Strategi Digital Marketing Berbasis EWOM dan STP pada Brand Skincare Pria Kahf di Jakarta Selatan (STMIK Dharmapala Riau, 2025)
This study aims to analyze the digital marketing strategy of Kahf in South Jakarta. Using a qualitative descriptive case study, data were collected through digital observation and content analysis of secondary sources. Findings indicate that Kahf adopts an STP approach, targeting young urban men, and implements a Digital Marketing Funnel from awareness to conversion. Social media platforms (TikTok, Instagram) and e-commerce (Shopee) are leveraged to deliver relevant content and expand market reach. Electronic Word of Mouth (E-WOM), particularly through consumer reviews, video content, and organic interactions, strengthens brand trust and positions Kahf as a halal, modern skincare product aligned with consumer needs. Despite having fewer followers, Kahf demonstrates higher engagement compared to competitors. Key challenges include dependence on TikTok and limited penetration among adult male segments. Overall, Kahf maintains a strong balance between brand image and consumer engagement, ensuring competitiveness in the men’s digital skincare market